2014
DOI: 10.1111/anec.12197
|View full text |Cite
|
Sign up to set email alerts
|

P‐Wave Duration in Lead aVR and the Risk of Atrial Fibrillation in Hypertension

Abstract: Simple measurement of PW duration in lead aVR allows effective identification of AF patients in a population of hypertensives. Confirmation of this finding in a larger population would provide a simple and effective risk marker of AF in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Chá vez et al investigated the relationship between blood pressure, LV mass index, and P-wave dispersion in a pediatric population and reported increased P-wave dispersion in pre-and hypertensive children, and a dependence of the P-wave dispersion on the LV mass index [41]. In the same line, Francia et al reported that a simple measurement of P-wave duration in lead aVR allows effective identification of AF risk in a population of hypertensive patients [42].…”
Section: Hypertensionmentioning
confidence: 99%
“…Chá vez et al investigated the relationship between blood pressure, LV mass index, and P-wave dispersion in a pediatric population and reported increased P-wave dispersion in pre-and hypertensive children, and a dependence of the P-wave dispersion on the LV mass index [41]. In the same line, Francia et al reported that a simple measurement of P-wave duration in lead aVR allows effective identification of AF risk in a population of hypertensive patients [42].…”
Section: Hypertensionmentioning
confidence: 99%
“…Prolongations of the PR interval and of several P‐wave indices derived from the 12‐lead resting electrocardiogram (ECG) have been proposed as intermediate phenotypes to mark this atrial remodeling process . Several studies have found that these ECG measures are associated with an increased risk of new‐onset AF and are also independently associated with obesity , metabolic syndrome , and HTN status . As obesity and HTN have a high prevalence and often coexist, we hypothesized that their single and joint effects on atrial remodeling would be reflected in the PR interval and P‐wave durations.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated atrial pressure due to card‐iac and noncardiac conditions, ischemia and metab‐olic stress cause atrial remodeling thus provide a substrate for atrial fibrillation . Hypertension, diastolic dysfunction, diabetes, advanced age, and increased BMI were found to be associated with prolongation of P‐wave indices due to atrial remodeling …”
Section: Discussionmentioning
confidence: 99%